O77: DOES MESH IMPROVE PATIENT SATISFACTION AND HEALTH-RELATED QUALITY OF LIFE AFTER IMPLANT-BASED BREAST RECONSTRUCTION? A MULTICENTRE PROSPECTIVE COHORT STUDY. (27th April 2021) - Sewart, E; Turner, N; Conroy, EJ; Cutress, R; Skillman, J; Whisker, L; Thrush, S; Barnes, N; Holcombe, C; Potter, S
Abstract: Introduction: Biological and synthetic meshes may improve outcomes of immediate IBBR by facilitating single-stage direct-to-implant procedures. However, high-quality supporting evidence is limited, particularly regarding PROs. Method: 2108 consecutive women undergoing IBBR at 81 centres were prospectively recruited between 2014-2016. Demographic, operative, oncological and 3-month complication data were collected. An 18-month questionnaire assessed PROs using the validated BREAST-Q and a five-point Likert scale rating of overall reconstructive outcome. The impacts of different IBBR techniques on PROs were explored using mixed-effects regression models adjusted for clinically-relevant confounders and including a random effect to account for clustering by centre. The reference group was two- stage submuscular reconstruction without mesh. Result: 1470 participants consented to receive the questionnaire and 891 completed it. 67 patients underwent two-stage submuscular reconstruction; 764 patients received subpectoral reconstructions with biological mesh (n=495) synthetic mesh (n=95) or dermal sling (n=174). 14 patients underwent prepectoral reconstructions (introduced late in the study). Compared with two-stage reconstructions, no differences in PROs were seen in biological or synthetic mesh-assisted or dermal sling procedures (p>0.05). However, prepectoral IBBR patients reported better satisfaction with breasts (difference=6.63, 95% confidence interval[1.65–11.61], p=0.009). Outcomes were similar to those in the NMBRA 2008/9 cohort, which included submuscular procedures only. Conclusion: This study does not suggest that mesh improves PROs of IBBR. It provides early data supporting improved satisfaction with breasts following prepectoral reconstructions. Future trials are needed to robustly evaluate prepectoral techniques. Abbrev: IBBR: implant-based breast reconstruction, PRO: patient-reported outcome, NMBRA: National Mastectomy and Breast Reconstruction Audit Take-home message: Although mesh-assisted techniques have become widely adopted, this large, prospective, multicentre cohort study does not suggest that mesh improves patient-reported outcomes of implant-based breast reconstruction compared with standard submuscular techniques. However, it provides early data to support improved satisfaction with breasts in the prepectoral setting, which now requires robust evaluation.